Biochemical Studies on Crab Scylla Serrata - GEORGE, CHINNAMMA; GOPAKUMAR, K. (Fishery Technology, 2017)
Studies on the biochemical composition of crab meat from body and claw revealedmarked differences in relation to :flavour. Protein content is on the higher side in crabs (19.1 to 20.9 ~lo) with high percentage of free amino acids and phosphorus and less carbohydrate and fat. The variation in composition due to the presence of eggs in female crabs and the importance of claw liquor and its composition are reported.